Redescription of brennanacarus annereauxi (Trombidiformes: Trombiculidae) with new records for Uruguay - Bassini-Silva, Ricardo; Huang-Bastos, Matheus; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP]; De Castro Jacinavicius, Fernando (Oxford University Press (OUP), 2021)
Brennanacarus annereauxi (Brennan and Yunker, 1969) was described from Venezuela parasitizing the greater spear-nosed bat. The monotypic genus Brennanacarus Goff, Yunker and Wheeler, 1987 is a replacement name for Nasicola Brennan and Yunker, 1969, which was preoccupied by Nasicola Yamaguti, 1968. Here, we redescribe the genus Brennanacarus and the type species B. annereauxi. Also, this is the first record of this species, as well as the second record of any chigger, for Uruguay.
Keywords: Chigger mite; Chiroptera; Ectoparasite; New record; South America